PENINGKATAN KEMAMPUAN PENALARAN MATEMATIS MAHASISWA CALON GURU MATEMATIKA MELALUI BLENDED-LEARNING DENGAN STRATEGI PROBING-PROMPTING: Blended-Learning:Probing-Prompting:Penalaran Matematis - Dahlia Fisher (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2017)
Blended learning is a learning method that combines two or more learning method. The objective of this research is to know the improvement of mathematical reasoning ability of student of mathematics prospective teacher, through Blended Learning with Probing-prompting learning strategy. The research method used is quantitative research, and divides participants into two groups. The first group is the experimental class group, it is the group of prospective teachers who get Blended Learning with Probing-Prompting Strategy and the second group is the control group; which is prospective teachers who get conventional learning. The study was conducted on 6th semester prospective teacher students from one university in Bandung, West Java, Indonesia. Based on this research, it is known that: experimental class group; which is the group of prospective teachers who get Blended Learning has improved the ability of mathematical reasoning is better than the control class group. It can be seen from the results of the normalized gain calculation of the experimental class reaches an average of 0.50 while the normalized gain of the control class reaches an average of 0.34. Although both are still in medium category, but based on t-test results between two parties, found that the increase has significant differences.